Law and Economic Performance in the Roman World - Erdkamp, Paul,; Verboven, Koenraad, (Impact of Empire ;, 2022)
Were legal systems in the Roman empire conducive to economic growth and development? Were legal rules and procedure changed in response to economic needs? This book offers detailed studies to provide some answers to these basic questions.